Quantitative susceptibility mapping: current status and future directions - Haacke, E. Mark; Liu, Saifeng; Buch, Sagar; Zheng, Weili; Wu, Dongmei; Ye, Yongquan (Magnetic resonance imaging, 2015)
Quantitative susceptibility mapping (QSM) is a new technique for quantifying magnetic susceptibility. It has already found various applications in quantifying in vivo iron content, calcifications and changes in venous oxygen saturation. The accuracy of susceptibility mapping is dependent on several factors. In this review, we evaluate the entire process of QSM from data acquisition to individual data processing steps. We also show preliminary results of several new concepts introduced in this review in an attempt to improve the quality and accuracy for certain steps. The uncertainties in estimating susceptibility differences using susceptibility maps, phase images, and T2* maps are analyzed and compared. Finally, example clinical applications are presented. We conclude that QSM holds great promise in quantifying iron and becoming a standard clinical tool.